Arrowroot, its processing and use in gastronomic preparations (Research, Society and Development, 2021)
The present work had as objective to characterize the botanical part of the arrowroot (Maranta arundinacea L.), by means of a bibliographical revision, and to describe the processing of the starch and of three different classifications of flours, being them: yellow, white and integral. The characteristics of the forms of reforestation of arrowroot, which carries cultural value, and its forms of consumption and applications were described. In addition, an overview was made of the centesimal composition of the arrowroot starch compared to other types of starches, showing its great potential for use in gastronomic preparations. Two preparations were emphasized: arrowroot cookie with coconut and pastry dough. In the elaboration of the cookie made from arrowroot starch with the addition of coconut, at the end of the preparation, a light colored cookie was observed, of aerated consistency, with a certain fragility, being crunchy, light and with a slightly sweet flavor. And in the preparation of the arrowroot pastry, at the end of the preparation, it was observed a light, crispy pastry that presented a better sensory quality when fried in oil with a relatively low temperature. Therefore, with the absence of gluten in the rhizome, it becomes feasible to consume for people with celiac disease, becoming another option for the production of foods that can be directed to people with dietary restrictions or not.